Bóg-człowiek-przyroda we współczesnych koncepcjach rozwoju nauki - Abdank-Kozubski, Andrzej (Śląskie Studia Historyczno-Teologiczne, 1993)
The author considers the extent and possible consequences of the appearance of classically meant truth in the positivistic and contemporary (represented by Popper and Kuhn) concepts of science development. The legacy of positivism is the scientific theory of cumulatism, according to which the truth is gradually approached by a systematic cumulation of particular scientific achievements. Such an outlook must give rise to trust in science and to a tendency of removing any barriers which might limit in any way the development of science. A more cautious attitude to science follows from the concepts of Popper and Kuhn. Revolutionary changes of paradigms show that science „may be wrong”. The relation between science and truth appears thus quite vague and even disappears in the extreme version of Kuhn. This often results in distrustful attitudes towards science and also in parascientific preferences. It is supposed, that the real image of science is still beyond the positivistic, as well as the Popper's and Kuhn's concepts. The proposal of a philosophical synthesis of scientific, metaphysical and religious images of the reality seems to be one of the possible ways of understanding the true status of science.